Eliciting paleographers' needs and modeling a collaborative workspace for digital library Malay manuscripts / Zahidah Zulkifli - Zulkifli, Zahidah (2013)
The purpose of this research is to instrument the support for Malay manuscript community (paleographers) in teaching, learning and doing research on manuscript in an electronic environment utilizing an available digital library of Malay manuscripts. The main objectives of this study are to: (i) investigate the current process of teaching, learning and researching manuscripts in Malay manuscript community that mainly involve lecturers, students and researchers (or known as paleographers); (ii) investigate what are the issues and challenges related to teaching, learning and researching in manuscript studies community; (iii) propose a new environment as a solution that can support and improve the process of teaching, learning and researching in manuscript studies; (iv) evaluate the usability of the suggested solution and gain insight from the paleographers on its effectiveness. Soft System Methodology (SSM) was employed throughout the study using a case study approach conducted at the Academy of Malay Studies (APM), University of Malaya (UM). The data was obtained from several interview sessions, focus group discussions and observations. The findings highlighted a number of issues in the process of teaching, learning and researching manuscripts mainly on the transliteration work, difficulties to find the original manuscripts for the study and locating an expert paleographer for consultation purpose. As a result, a conceptual model of an electronic platform (named as E-Workspace) for learning and collaborative research activities for Malay manuscripts was proposed to improve the current practise. The E-Workspace was modelled to focus on facilitating the manuscript community in teaching, learning and researching Malay manuscripts, particularly in transliteration work. The usability of the E-Workspace in providing a teaching, learning and research platform that are conducive for the manuscript studies are reflected by the positive feedback on the user evaluation. The E-Workspace in general enhances the utilization of MyManuskrip as a resource that supports teaching, learning and researching manuscripts by providing a collaborative platform to conduct transliteration works electronically.